Peningkatan Nilai Nutrisi Pollard melalui Fermentasi Ragi Tempe sebagai Bahan Pakan Buatan Ikan Nila (Oreochromis niloticus) [ Increased Nutritional Value Pollard Through Yeast Fermentation Tempe as Artificial Feed Ingredients Tilapia (Oreochromis niloticus)] - Gunanti Mahasri; Miftakhul Munir; Romziah Sidik (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract Tilapia (Oreochromis niloticus) is a type of fish that is easily cultivated in various places (pond, floating cage and rice fields). Pollard is an alternative feed ingredients that have great potential, both as a source of energy, crude fiber source, or sources other macro nutrients. Mold in fermentation used and contributes to a feed enzymes that help digestion and to penetrate into the network feed that network structure becomes brittle and breaks down and the surface becomes more widespread. more surface enables direct contact with digestive enzymes cellulose greater. The results of the analysis of the nutrient content of food research trials show that using tempeh fermentation pollard 0.2% can increase the nutritional value of protein pollard 14.88%. Pollard tempeh fermentation using 0.2% can improve the digestibility of crude fiber and digestibility of dry matter pollard. Feed consumption of tilapia in the treatment using fermented tempeh pollard 0.2% is not significantly different from the commercial feed. Pollard tempeh fermentation using 0.2% to 16.98% protein content can increase the growth rate of tilapia.